The Role of Gender and Acculturation Attitudes in Predicting the Second-Generation Indonesian Migrants’ Adaptation in Malaysia - Jamaludin, Nor Lelawati; Farradinna, Sharifah; Barna, Eshaq Ali (Advances in Social Sciences Research Journal, 2023)
The present study’s aims were to test second-generation Indonesian migrants’ attitudes toward their home culture and toward host culture as a necessary component of inclusion for society and to determine whether these acculturation attitudes (attitudes towards home and host culture) moderate the relationship between gender and acculturation outcomes (psychological adaptation and sociocultural adaptation) using a group of N=105 second-generation Indonesians in Malaysia. Structural Equation Model-AMOS was conducted to test the relationship among variables. The findings imply that among second-generation Indonesian migrants, the two fundamental aspects of acculturation attitudes (attitudes towards home and host culture) were mainly independent. The association between gender and sociocultural adaption is moderated by acculturation attitudes. The connection between acculturation attitudes and psychological adaptation was, in turn, mediated by sociocultural adaptation. The findings also demonstrated that sociocultural and psychological adaptation each had distinct predictors. Gender directly predicted psychological adaptation, whereas acculturation attitudes (attitudes towards home and host culture) directly impacted sociocultural adaptation.